2021
DOI: 10.1155/2021/6591784
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease-Associated Liver Fibrosis Is Linked with the Severity of Coronary Artery Disease Mediated by Systemic Inflammation

Abstract: Background and Aim. Nonalcoholic fatty liver disease (NAFLD) is an independent risk factor for cardiovascular disease. Hepatic fibrosis is the most significant determinant of all-cause- and liver -related mortality in NAFLD. However, the relationship between NAFLD fibrosis and severe coronary artery disease (CAD) remains unclear. Methods and Results. We conducted a retrospective study of 531 patients with ultrasonogram-confirmed NAFLD who underwent percutaneous coronary intervention (PCI). Then, all patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…(a) fast decongestion, which may cause an immediate reduction in HHF, and/or (b) a high FIB-4 score associated with NAFLD may also be a reflection of systemic inflammation, fibrosis and associated CVDs. 47 Preclinical animal model data for finerenone showed anti-inflammatory and antifibrotic effects, 48 and although the clinical translation may be complex, the systemic antifibrotic effects may be effective in the long-term, particularly in patients with elevated fibrosis markers. Moreover, finerenone has fewer side effects compared with other MRA antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…(a) fast decongestion, which may cause an immediate reduction in HHF, and/or (b) a high FIB-4 score associated with NAFLD may also be a reflection of systemic inflammation, fibrosis and associated CVDs. 47 Preclinical animal model data for finerenone showed anti-inflammatory and antifibrotic effects, 48 and although the clinical translation may be complex, the systemic antifibrotic effects may be effective in the long-term, particularly in patients with elevated fibrosis markers. Moreover, finerenone has fewer side effects compared with other MRA antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidemia is a strong pathological consequence of inflammatory responses in the hepatic pathologies associated with MetS [ 60 , 61 , 62 ]. NAFLD is a type of steatosis, where >5% ectopic fat accumulates in the liver in the absence of competing etiologies such as heavy alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that high FS associates with incidence of coronary heart disease [ 31 , 32 ] as well as the angiographic complexity [33] , [34] , [35] , risk of MACE [ 34 , 36 ], and death [37] in patients with established coronary heart disease. In an analysis of the IMPROVE-IT trial that compared ezetimibe with placebo in patients with ACS treated with simvastatin [36] , high FS (>0.67, n=2,106) vs low FS (<-1.455, n=5,440) was associated with 30% increased risk of MACE.…”
Section: Discussionmentioning
confidence: 99%